Study the preventive effect of aqueous extract of Gingko biloba on cerebral damage induced by ischemia/ reperfusion in rat - Mohammed, Mustafa T. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: cerebral damage may occur in a variety of clinical settings and this remains a significant problem. Therefore, it seems possible that the administration aqueous extract of Gingko biloba might protect the brain against the ischemia reperfusion injury.Objectives: The study included knowledge Phytochemical Composition and determine whether Gingko biloba in the aqueous extract prevents or decreases I/R brain damage.Methods: Thirty rats were divided into three groups as control, I/R group and Gingko biloba treatment group. Serum was used for the estimation of biochemical parameters: oxidative stress levels of nitric oxide (NO) and lipid peroxidation (LPO) and blood was used for the estimation of enzyme immunoassay: Interleukin-8 (IL-8), tumor necrosis factor Alpha (TNF-α), interleukin-1β (IL-1β).Results: The results showed that the extract contain : glycosides , saponins ,tannins ,phenolic compounds , resins, flavonoids ,alkaloids and proteins.The levels of Oxidative stress in group 3 were significantly lower than those in group 2 as well as the levels of enzyme immunoassay in group 3 were significantly lower than those in group 2.Conclusion: The present results suggest that Gingko biloba treatment protects the rat brain against ischemiareperfusion brain damage.